2004
DOI: 10.1094/mpmi.2004.17.1.34
|View full text |Cite
|
Sign up to set email alerts
|

NPR1-Independent Activation of Immediate Early Salicylic Acid-Responsive Genes in Arabidopsis

Abstract: Salicylic acid (SA) is a key signal for the activation of defense genes in response to stress. The activation of late defense genes by SA, such as PR-1, involves the participation of the NPR1 protein. This protein acts as coactivator of the TGA factors that recognize as-1-like elements in the PR-1 promoter. Considering that functional as-1-like elements are also found in the promoter of SA- and auxin-responsive immediate early genes, we tested the hypothesis that NPR1 is also required for activation of these g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
81
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 54 publications
17
81
1
3
Order By: Relevance
“…5), suggesting this motif may be active. In addition, the glucosyltransferase UGT73B1 (At4g34138) identified by our microarray studies contains an as-1-like element in its upstream region and was also shown recently to be induced by 2,4-D and salicylic acid (88), suggesting a potential role for these elements in the activation of some Arabidopsis glucosyltransferase promoters during xenobiotic stress. Inspection of the upstream regions for the remaining 10 UGTs shown in Table III revealed only one additional UGT gene (UGT75B1; At1g05560) containing an as-1-like element on the "Ϫ" strand (not shown); however, steady-state mRNA levels for this UGT were unresponsive to 10 M 2,4-D treatments and exhibited only modest increases (ϳ3-fold) in response to 100 M treatments (Fig.…”
Section: Response Of Selected Genes To Xenobiotics and Inducers Of Xesupporting
confidence: 54%
“…5), suggesting this motif may be active. In addition, the glucosyltransferase UGT73B1 (At4g34138) identified by our microarray studies contains an as-1-like element in its upstream region and was also shown recently to be induced by 2,4-D and salicylic acid (88), suggesting a potential role for these elements in the activation of some Arabidopsis glucosyltransferase promoters during xenobiotic stress. Inspection of the upstream regions for the remaining 10 UGTs shown in Table III revealed only one additional UGT gene (UGT75B1; At1g05560) containing an as-1-like element on the "Ϫ" strand (not shown); however, steady-state mRNA levels for this UGT were unresponsive to 10 M 2,4-D treatments and exhibited only modest increases (ϳ3-fold) in response to 100 M treatments (Fig.…”
Section: Response Of Selected Genes To Xenobiotics and Inducers Of Xesupporting
confidence: 54%
“…Thus, both leaf and root application of MeJA and SA led to the induced systemic GS response. This is in contrast to the B. oleracea in which only root JA application yielded a systemic response (van Dam et al, 2004).…”
Section: Discussioncontrasting
confidence: 56%
“…However, there are many exceptions to this basic framework, and recent works suggest that interactions between the JA and SA pathways may play important roles in finetuning defense responses (Takahashi et al, 2004;Flors et al, 2008;Smith et al, 2009;RobertSeilaniantz et al, 2011). SA-applications did not disturb the JA-induced GS accumulation in Brassica oleracea and Brassica nigra (van Dam et al, 2004), but attenuated in several Arabidopsis genotypes (Cipollini et al, 2004). All these studies were based on the separate pre-and post-treatment of the tissues with either SA or JA.…”
Section: Introductionmentioning
confidence: 99%
“…be:8080/PlantCARE). Interestingly, this sequence forms the core of the as-1 element found in the promoter of genes responding in a SA-dependent, NPR1-independent fashion (Uquillas et al, 2004). We additionally found several apparently novel motifs that have not yet been described as targets of known transcription factors (according to searches in the PlantCARE, TRANSFAC, and PLACE databases).…”
Section: Conserved Cis-elements Among Genes From the Same Categorymentioning
confidence: 83%